Sequential parallel comparison design for "gold standard" noninferiority trials with a prespecified margin. Issue 6 (28th August 2019) - Homma, Gosuke; Daimon, Takashi
Abstract: Three‐arm noninferiority trials (involving an experimental treatment, a reference treatment, and a placebo)—called the "gold standard" noninferiority trials—are conducted in patients with mental disorders whenever feasible, but often fail to show superiority of the experimental treatment and/or the reference treatment over the placebo. One possible reason is that some of the patients receiving the placebo show apparent improvement in the clinical condition. An approach to addressing this problem is the use of the sequential parallel comparison design (SPCD). Nonetheless, the SPCD has not yet been discussed in relation to gold standard noninferiority trials. In this article, our aim was to develop a hypothesis‐testing method and its corresponding sample size calculation method for gold standard noninferiority trials with the SPCD. In a simulation, we show that the proposed hypothesis‐testing method achieves the nominal type I error rate and power and that the proposed sample size calculation method has adequate power accuracy.